Pharamcotherapeutic management of hypertension in chronic kidney disease patients. - Sapkota, Yunima (2021)
ABSTRACT: Background: Hypertension (HTN) is a prominent co-morbidity being both a cause and a consequence of Chronic Kidney Disease (CKD). Often, blood pressure control has been a challenge in CKD patients and it has been found to worsen the clinical outcome leading to other cardiovascular (CV) effects. Methods: Cross-sectional descriptive study was carried out to study the pharmacotherapeutic management of HTN in CKD patients. CKD patients visiting the Nephrology outpatient department or receiving dialysis services and those who were prescribed antihypertensive drugs were included in the study. Inpatients were not included in the study due to the seriousness of comorbidities and CKD patients, diagnosed with HTN on the day of interview were also excluded from the study. Results: 119 CKD patients with hypertension were enrolled in the study. 43% patents belonged to the age group 41-60 years. Of them, 61% were males. Following the JNC- 8 Guidelines, only 30% of the patients met the target BP goal. Majority (36%) of the patients were prescribed dual therapy followed by mono therapy (27%), triple therapy (22%), combination of four (14%) and combination of five drugs (1%). The most commonly prescribed group of anti-hypertensive drugs for the treatment of hypertension in CKD patients were calcium Channel Blockers(79%), Loop Diuretics (47.9%), Alpha-1 Blocker (34.5%), Beta Blockers (30.3%0 , Alpha -2 Agoinst (17.6%), Angiotensin Receptor Blockers (8.4%), Alpha plus Beta Blockers (3.4%) and Angiotensin Converting Enzyme Inhibitors (0.8%). Only 4% of the total medicines were prescribed as Fixed-dose combinations (FDCs) and only 2.5% prescriptions were written in generic name. The median cost for antihypertensive treatment in a day was found to be NRs. 29. The cost was found higher in case of patients in uncontrolled BP group. Conclusion: Well management of hypertension can show down the progression of CKD and also prevent cardiovascular and cerebrovascular complications of hypertension. Management of hypertension is a challenge, especially when it is associated with CKD. The costs of uncontrolled hypertension in CKD are high in terms of both disease burden and expenditure. Multiple medications have to be prescribed to lower the blood pressure to achieve target BP level a lot of times. Sometimes, even with maximal tolerated dose of multiple medications, target blood pressure cannot be achieved. The best way to manage this situation is preventing the occurrence of hypertension and CKD. Findings cases before they progress to later stages and slowing the progression of CKD also helps. The health seeking behavior of the population should also be considered. Even after patients progress to later stages, implementation of guidelines and adherence to those by clinicians helps in preventing the burden of ESRD and other complications of hypertension. Policy makers have to focus more on preventing the occurrence of CKD along with managing ESRD.